Verification of the structure of psychological well-being in a representative Lithuanian sample - Kairys, A.; Liniauskaitė, A.; Bagdonas, A.; Pakalniškienė, V. (Psichologija, 2013)
Some studies focusing on well-being were unable to distinguish two – hedonic and eudaimonic – components of well-being (Vitterso et al., 2010; Kashdan et al., 2008; Šarakauskienė, 2012). Previous comparatively smaller sample researches, conducted by the authors of this article, also yielded a single psychological well-being phenomenon (Bagdonas et al., 2012; 2013). Although a slightly different structure was established, studies could not isolate two traditional – hedonic and eudaimonic – components. The aim of this study was to verify the structure of psychological well-being in a representative Lithuanian sample using the original Lithuanian Psychological Well-being Scale. Methods. 1202 Lithuanian citizens aged 16–89 were enrolled in the research (M = 45.5 years, SD = 18.7 years). The study sample was representative of the Lithuanian population aged from 16 to 89 years according to gender, age, educational level, nationality, type of settlement, and region. The Lithuanian Psychological Well-being Scale, which consists of seven subscales (optimism / control, satisfaction with living standards, negative affectivity, satisfaction with relatives, satisfaction with interpersonal relations, satisfaction with physical health, satisfaction with work) was used in this study. Two items that depict satisfaction with living in Lithuania were not included in the factor analysis. The analysis of the data was conducted using the SPSS 20 and structural equation modelling AMOS software. Results. The data obtained from the Lithuanian representative sample supports the same factor structure of the Lithuanian Psychological Well-being Scale (χ2 = 4851.0; df = 1487; p < 0.0001; RMSEA = 0.043; CFI = 0.9; TLI = 0.889) that was established by previous studies. The scale consists of optimism / control, satisfaction with living standards, negative affectivity, satisfaction with relatives, satisfaction with interpersonal relations, satisfaction with physical health, and satisfaction with work subscales. All the mentioned subscales have a high internal consistency (Cronbach α is no less than 0.8). The testing of the second-order factor models has shown that psychological well-being is a coherent and unanimous phenomenon; even when two second-order factors representing the hedonic and eudaimonic aspects of well-being are omitted in the model, the correlation between those two is very high (>0.8). The obtained results do not support the idea that the construct of well-being consists of two different foci; it seems like there is no hedonic or eudaimonic well-being, but just a person’s psychological well-being.